Determination of power loss in compressor stage of turbogenerator in dynamic experiments - D. А. Kalashnikov; А. S. Pugachuk; E. О. Chudotvorova; A. V. Chernyshev (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение", 2018)
A mathematical model for the interaction of a gas environment with the surfaces of the impeller of turbogenerator compressor is developed. The study of the characteristic of power losses at various rotational speeds of the rotor is provided. Recommendations for testing the impeller of turbogenerator compressor is given